Spillover effects in seeded word-of-mouth marketing campaigns - Chae, I; Stephen, A; Bart, Y; Yao, D (INFORMS, 2016)
Seeded marketing campaigns (SMCs) involve firms sending products to selected customers and encouraging them to spread word of mouth (WOM). Prior research has examined certain aspects of this increasingly popular form of marketing communication, such as seeding strategies and their efficacy. Building on prior research, this study investigates the effects of SMCs that extend beyond the generation of WOM for a campaign’s focal product by considering how seeding can affect WOM spillover effects at the brand and category levels. The authors introduce a framework of SMC-related spillover effects, and empirically estimate these with a unique data set covering 390 SMCs for products from 192 different cosmetics brands. Multiple spillover effects are found, suggesting that while SMCs can be used primarily to stimulate WOM for a focal product, marketers must also account for brand- and category-level WOM spillover effects. Specifically, seeding increases conversations about that product among nonseed consumers, and, interestingly, decreases WOM about other products from the same brand and about competitors’ products in the same category as the focal product. These findings indicate that marketers can use SMCs to focus online WOM on a particular product by drawing consumers away from talking about other related, but off-topic, products.